Exploring Cognitive Processes of Teachers in the Open-Ended Learning Environment - (:unkn) unknown (My University, 2011)
This study explores professional learning of teachers in a web-based Open-Ended Learning Environment (OELE). Adult learning theorists suggest that adults are self-directed, experience-based, personally- and socially-related, problem-oriented, and application-focused learners. Constructivists suggest that the OELE affords learners opportunities to construct knowledge by engaging in mental and cognitive processing on an individual level and social-dialogical negotiation among learners, thus, the OELE promotes high levels of cognitive functioning. However, current research has not yet provided any direct observation on the learning processes that mediate the cognitive functioning of a teacher's professional learning in the OELE. Therefore, six teachers were selected and think-aloud protocols were employed in this study to explore the nature of their thought processes in the context of independent and group learning. The results indicated individual differences in demonstrating conceptual understanding, applicability, and authentic discernment when solving authentic problems through interacting with learning content, peers, and instructors. Some suggestions were made pertaining to instructional conditions that fostered professional growth of teachers in web-based, OELE training.
Keywords: Elementary school teachers--In-service training; Web-based instruction; Cognitive learning; Verbal learning; Elementary school teachers--Psychology; Constructivism (Education)